2022
DOI: 10.1111/ctr.14755
|View full text |Cite
|
Sign up to set email alerts
|

Formation of donor‐specific antibodies depends on the epitope load of mismatched HLAs in lung transplant recipients: A retrospective single‐center study

Abstract: The development of donor-specific antibodies (DSA) has a significant impact on graft outcome in solid organ transplantation. Mismatched HLAs are recognized directly and indirectly by the recipient immune system. Both pathways occur in parallel and result in the generation of plasma cells, DSA, cytotoxic and T helper lymphocytes. Here, we present the results of an analysis of the epitope load of mismatched HLAs in a cohort of 220 lung transplant recipients using two in silico algorithms, HLAMatchmaker and PIRCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Among others, they incorporated the following features: estimated glomerular filtration rate, proteinuria, histology, and HLA antibody [42]. Furthermore, recently advanced approaches based on neural networks making use of large proteomic databases occurred for assessment of immunogenicity and probability to generate antibodies [27,43,44].…”
Section: Using ML For Cpmsmentioning
confidence: 99%
“…Among others, they incorporated the following features: estimated glomerular filtration rate, proteinuria, histology, and HLA antibody [42]. Furthermore, recently advanced approaches based on neural networks making use of large proteomic databases occurred for assessment of immunogenicity and probability to generate antibodies [27,43,44].…”
Section: Using ML For Cpmsmentioning
confidence: 99%
“…One study by Kulkarni and colleagues found an independent link between the growth of Pseudomonas aeruginosa, but not other organisms, on respiratory cultures and later development of DSAs, hypothesizing that the particularities of the immune response to Pseudomonas promotes an inflammatory milieu that promotes DSA formation ( 19 ). More recently, there has been considerable interest in the use of computer algorithms to estimate the risk of de novo DSA development on the basis of pre-transplant epitope mismatch loads ( 20 , 21 ).…”
Section: Clinical Implications Of Donor-specific Hla Antibodiesmentioning
confidence: 99%
“…PIRCHE II is a sophisticated implementation of this approach that generates a score for each donor antigen in the context of each recipient HLA class II allele, representing the number of unique, non-self, core sequences from the donor antigen that are expected to bind to and be presented by the recipient HLA (117). In just the past few years, PIRCHE II scores have been associated in studies of kidney, lung, cardiac, and liver transplant recipients with increased risk of DSA and TCMR (164)(165)(166)(167).…”
Section: Immunopeptidomementioning
confidence: 99%